Sensitivity analysis of parameters affecting suspended growth in industrial wastewater treatment plants; with emphasis on economic performance criteria - Mohammad Gheibi; Benyamin chahkandi; Zahra Kian; Amir Takhtravan; Reza Aghlmand (Annals of Environmental Science and Toxicology - Peertechz Publications, 2021)
Industrial wastewater treatment is of high priority due to the presence of an extraordinary concentration of dangerous pollutants. Similar to urban wastewater treatment plants, there are plenty of options while designing industrial ones which need various analyses and researches to choose correctly. One of the most efficient ways to solve this problem is to implement Economic and Sensitivity Analysis. This research has studied designing an industrial wastewater treatment plant utilizing three different biological treatment methods (including Sequential Batch Reactors (SBR), plug-flow activated sludge with a secondary clarifier, and step aeration activated sludge with a secondary clarifier). It also measures the sensitivity of performance cost parameters to factors affecting the suspended growth unit. The results of the economic analysis showed that using SBR has the highest construction cost of $ 70,200,000 and the highest total cost of 96,900,000. Sensitivity analysis showed that by adjusting design retention time and variance between heterotrophic microorganism decay rate and the reality, using activated carbon-based systems could significantly reduce total annual costs.